1997
DOI: 10.1046/j.1365-2249.1996.d01-909.x
|View full text |Cite
|
Sign up to set email alerts
|

Escape of HIV-1 is associated with lack of V3 domain-specific antibodies in vivo

Abstract: SUMMARYThis study was performed to analyse correlates of viral escape in AIDS patients. Peripheral blood mononuclear cells (PBMC) from HIV ¹ donors were inoculated with AIDS patients' serum to detect neutralization-resistant cell-free virus. Infectious virus was detected by polymerase chain reaction (PCR) and analysed by sequencing the V3 region. The escaped virus species was compared with all V3 virus variants found in the patients' PBMC and plasma. In one patient escaped virus was also compared with variants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

1999
1999
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 35 publications
0
13
0
Order By: Relevance
“…This has particularly been described for the V3 loop [39,53,89]. While some authors describe a lack of V3-specific neutralizing antibodies in patients who develop AIDS [89], others have found that neutralizing antibodies for one strain of HIV-1 to the V3 loop could fail to neutralize another strain of the same virus and even enhance infection in a third strain [53]. These findings have identified the variable position 311 proximal to the conserved GPGR motif at the top of the V3 crown as important for viral sensitivity to neutralization or enhancement by antibodies.…”
mentioning
confidence: 84%
See 1 more Smart Citation
“…This has particularly been described for the V3 loop [39,53,89]. While some authors describe a lack of V3-specific neutralizing antibodies in patients who develop AIDS [89], others have found that neutralizing antibodies for one strain of HIV-1 to the V3 loop could fail to neutralize another strain of the same virus and even enhance infection in a third strain [53]. These findings have identified the variable position 311 proximal to the conserved GPGR motif at the top of the V3 crown as important for viral sensitivity to neutralization or enhancement by antibodies.…”
mentioning
confidence: 84%
“…It is thought that these loops change in structure and conformation from time to time, thereby allowing the virus to elude the immune response. This has particularly been described for the V3 loop [39,53,89]. While some authors describe a lack of V3-specific neutralizing antibodies in patients who develop AIDS [89], others have found that neutralizing antibodies for one strain of HIV-1 to the V3 loop could fail to neutralize another strain of the same virus and even enhance infection in a third strain [53].…”
mentioning
confidence: 97%
“…3). Many mutations were located in V3, a region that contains linear and discontinuous antigenic determinants (9,18,39) that can change during disease development and immune escape (37,38,41). Some amino acid substitutions led to three new and loss of two potential N-linked glycosylation sites, which in turn might result in changes in conformation and immune recognition of gp120 (3,12,14,29,30,35,47,50).…”
Section: Nonpassaged Shiv-vpumentioning
confidence: 99%
“…Serum adsorption studies have shown that type-specific V3-directed antibodies contribute to the neutralization of autologous virus and control of in vivo infection for some patients (6,41,42). The existence of V3 epitopes that mediate the neutralization of primary virus isolates and are conserved within clade B was shown by the demonstration that polyclonal V3-reactive antibodies isolated from North American patient sera possessed potent neutralizing activity against a number of clade B primary isolates (26).…”
mentioning
confidence: 99%